Faktor-Faktor Yang Mempengaruhi Speech Delay Pada Anak Usia Dini Di Posyandu X Kelurahan Kutabaru : Factors Affecting Speech Delay in Early Childhood at Posyandu X Kutabaru Village - Nurmayanti; Mariyani (Dohara POAJ, 2023)
Introduction: Barriers to later speech development can not only affect a child's social and personal adjustments but can also affect a child's academic adjustment. Due to the importance of the function of speech development in these children, this study attempts to describe what factors can influence the development of speech in children. The purpose of this study was to determine the factors associated with the occurrence of speech delay in early childhood at Posyandu X, Kutabaru District, Tangerang Regency in 2022. Method: The research method is quantitative analytic using cross-sectional. The statistical test used is the chi-square test. The research was conducted at Posyandu X, Kutabaru Village, Tangerang Regency in 2022. The number of samples was 60 people. The sample selection method is by total sampling, and the type of data used is primary data. Results: The results of the chi-square statistical test showed that the variables associated with the occurrence of speech delay were the mother's education (p-value 0,042) and the sex of the toddler (p-value 0,000) and the unrelated variable was parenting style (p-value 0,424). Discussion: For parents who answered that democratic parenting was dominant, it was good enough in raising their children, also authoritarian parenting, which was partially applied in parenting. So that children do not experience speech delays. For parents with boys who are diagnosed with a possible speech delay, it is best to follow up and deal with it immediately one of which is by providing stimulation from an early age.